Gentiopicrin exerts anti-rheumatic effect in human fibroblast-like synoviocytes via inhibition of p38MAPK/NF-ÎºB pathway - Zhang, Nian; Jiang, Yi; Mu, Fangxiang; Wu, Hong; You, Qingxia (Cellular and Molecular Biology, 2019)
To investigate the effect of gentiopicrin on the expressions of inflammatory factors in human fibroblast-like synoviocytes (HFLS) and the underlying mechanism. Human fibroblast-like synoviocytes (HFLS) were cultured in vitro at 37 °C in Dulbecco's modified Eagle's medium (DMEM) supplemented with 5 % fetal bovine serum (FBS) in a humidified incubator containing 5 % CO2. Cell viability was determined using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-tetrazolium bromide (MTT) assay, while real-time quantitative polymerase chain reaction (qRT-PCR) was used to determine the expressions of interleukin 1Î² (IL-1Î²) and interleukin 6 (IL-6) mRNAs. The expressions of p38 mitogen-activated protein kinase (p38 MAPK) and nuclear factor kappa light chain enhancer of activated B cells (NF-ÎºB) were determined using Western blotting. Enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of IL-1Î² and IL-6 in cell lysate. Treatment with 5-25 Î¼M gentiopicrin did not significantly affect the number of viable cells, when compared with control group (p > 0.05). However, at 50 and 100 Î¼M gentiopicrin, the number of viable cells were significantly increased, relative to control group (p < 0.05). Results of qRT-PCR showed that the expression levels of IL-1Î² and IL-6 mRNAs were significantly higher in TNF-Î± group than in control group (p < 0.05). However, treatment with gentiopicrin significantly and dose-dependently decreased their expression levels compared with TNF-Î± group (p < 0.05). Western blotting results showed that the expressions of p-p38MAPK and NF-ÎºB-p65 proteins were significantly upregulated in TNF-Î± group, when compared with control group (p < 0.05). However, treatment with gentiopicrin significantly and dose-dependently down-regulated the expression of these proteins compared with TNF-Î± group (p < 0.05). The levels of IL-1Î² and IL-6 in cell lysate were significantly higher in TNF-Î± group than in control group (p < 0.05). However, treatment with gentiopicrin, and p38MAPK/NF-ÎºB pathway inhibitors (SB203580 and BAY11-7082) significantly reduced the levels of these inflammatory factors compared with TNF-Î± group (p < 0.05). Gentiopicrin has therapeutic potential for Rheumatoid arthritis (RA ) through a mechanism involving the inhibition of p38MAPK/NF-ÎºB pathway.